Institutional Environment, Bank Stability and Economic Growth in the Middle East and North Africa - (:unkn) unknown (My University, 2015)
The Middle East and North Africa (MENA) region has witnessed many institutional and financial reforms meant to stimulate economic development. While traditional theories of economic growth promote capital accumulation and technological progress as fundamental determinants of economic development, studies that gave birth to the “new institutional economics” stress the major contribution of institutional development to economic development. The objective of this dissertation is to understand the role of institutional quality and financial regulation in the process of financial development and economic growth in the MENA region since the 1980s. Based on recent and adequate econometric models, this dissertation answers the following questions: What is the role played by institutional quality and banking regulation in explaining capital, risk and efficiency adjustments in the banking system of the MENA region? Is there a positive and significant effect of institutional quality on banking and economic development? Can inter-country differences in terms of economic performance be explained by institutional factors? significant effect on bank capital, excessive risk taking and efficiency of banks operating in the MENA region; (ii) Banking regulation has a positive and significant effect on banking development, and there is positive and significant interdependence between economic growth and banking development; (iii) the impact of institutional quality is stronger in countries that witnessed a weak growth rate on average compared to fast-growing countries where the institutional effect is not significant.
Keywords: African Research